A study on the intention to use mobile fintech services among Gen Z in Malaysia. - Nur Damia Zahidah Khairil Amin; Nur Syahira Mustafa; Nur Zainina Hastiera Harun; Nurul Hidayah Hanis Rosli (2024)
Many studies are related to financial technology (Fintech). However, there is still a lack of studies that focus on Generation Z, especially their intention to use the services, while this generation is familiar and is easily adaptable to new technology. This study focuses on the relationship between Gen Z’s behavioral intention to use Mobile Fintech Services and Performance Expectancy, Effort Expectancy, Social Influence, and Facilitating Conditions. In addition, contributes by researching Gen Z’s behavioral intention to use Mobile Fintech Services in Malaysia. The UTAUT model was used in this study. Quantitative approaches of 412 Generation Z people participated in this study using Spearman correlation, and the data was analyzed using SPSS. The findings revealed that the Spearman Correlation value for all independent variables has a strong positive relationship with Gen Z’s behavioral intention to use Mobile Fintech Services (Sig <. .05) with Performance Expectancy (0.816), Effort Expectancy (0.606), Social Influence (0.859), and Facilitating Conditions (0.827). This study concludes that service providers have to pay attention to these relationships in attracting Generation Z.